Shape Tailored Magnetic Nanorings for Intracellular Hyperthermia Cancer Therapy. Issue 1 (December 2017) - Dias, Carlos; Hanchuk, Talita; Wender, Heberton; Shigeyosi, Willian; Kobarg, Jörg; Rossi, André; Tanaka, Marcelo; Cardoso, Mateus; Garcia, Flávio
Abstarct This work explores a new class of vortex/magnetite/iron oxide nanoparticles designed for magnetic hyperthermia applications. These nanoparticles, named Vortex Iron oxide Particles (VIPs), are an alternative to the traditional Superparamagnetic Iron Oxide Nanoparticles (SPIONs), since VIPs present superior heating power while fulfilling the main requirements for biomedical applications (low cytotoxicity and nonremanent state). In addition, the present work demonstrates that the synthesized VIPs also promote an internalization and aggregation of the particles inside the cell, resulting in a highly localized hyperthermia in the presence of an alternating magnetic field. Thereby, we demonstrate a new and efficient magnetic hyperthermia strategy in which a small, but well localized, concentration of VIPs can promote an intracellular hyperthermia process.